A new protein-coupled antigen of α-conotoxin MI displays high immunogenicity and can produce antiserum with high detoxification activity. (March 2022) - Zhang, Min; Yu, Shuo; Zhang, Xin; Huang, Qiuyuan; Huang, Yue; Luo, Min; Wei, Yuanmei; Chen, Wenwen; Chen, Ze; Zhou, Xiaowei; Dai, Qiuyun
Abstract: α-conotoxin (α-CTX) MI is a small peptide toxin with 14 amino acids and two disulfide bonds. It potently inhibits muscle-type nicotinic acetylcholine receptors (nAChRs), and poses a threat as a toxin to tropical fishermen. However, there are currently no effective drugs for the treatment of MI envenomation due to the toxin's low immunogenicity. In this report, we generated neutralizing antiserum and F(ab')2 to MI by synthesizing a new MI antigen through the coupling of alkynyl-modified MI and azide-modified bovine serum albumin (BSA), followed by immunization into mouse and horse. The new MI-BSA antigen generated high titers of mouse and horse antiserum (1:204, 800 and 1:51, 200, respectively), and both the antiserum as well as the horse F(ab')2 displayed highly potent neutralization and detoxification efficacy. 12.5 μL of mouse or horse antiserum preincubated with MI could completely neutralize a lethal dose of the MI (0.4 μg, 1.7 × LD50 ), while 6.25 μL (mouse) or 10.41 μL (horse) of the antiserum could exert complete detoxification of mice injected with 1.7 × LD50 of MI. Moreover, the mouse and horse antiserum exhibited medium cross-reactivity for highly toxic α-CTX GI. These results demonstrate that the integrity of MI's antigen epitope and carrier effect of BSA can improve MI's immunogenicity, and provides an effective detoxification treatment for highly toxic α-conotoxins as well as an effective method for the preparation of antiserum of small peptide toxins. Graphical abstract: Image 1 Highlights: α-conotoxin MI-bovine serum albumin conjugate antigen was synthesized by click reaction. This antigen maintains the integrity of MI's antigen epitope. This antigen displays high immunogenicity. This antigen produces antiserum with high neutralizing and detoxification activity. The MI's antiserum possesses medium cross-reactivity to α-conotoxin GI.